2019
DOI: 10.1371/journal.pone.0222033
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in PXR and NF-κB1 influence susceptibility to anti-tuberculosis drug-induced liver injury

Abstract: Background Pregnane X receptor (PXR) regulates the expression of drug-metabolizing enzymes and transport enzymes. NF-κB not only plays a role in liver homeostasis and injury-healing processes by regulating inflammatory responses but may also regulate the transcription of PXR. Currently, genetic polymorphisms in PXR are associated with adverse drug effects. Because little is known about the association between NF-κB1 genetic polymorphisms and adverse drug reactions, we explored the association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…and ATDH susceptibility. [20][21][22][23][24] Using the fixed-effects model, the pooled estimates of the five included studies did not show a significant association between SNP rs3814055 and the risk of ATDH (dominant model, OR = 1.00, 95% CI: 0.82-1.22, P = 1.00, Figure 2;…”
Section: Quantitative Analysismentioning
confidence: 98%
See 4 more Smart Citations
“…and ATDH susceptibility. [20][21][22][23][24] Using the fixed-effects model, the pooled estimates of the five included studies did not show a significant association between SNP rs3814055 and the risk of ATDH (dominant model, OR = 1.00, 95% CI: 0.82-1.22, P = 1.00, Figure 2;…”
Section: Quantitative Analysismentioning
confidence: 98%
“…No further significant association was observed between these SNP polymorphisms and ATDH susceptibility ( Table 2, Figure S1-S8). The remaining 8 SNPs (ie, rs12488820, rs1523127, rs2276707, rs2461825, rs2472677, rs2472682, rs3732357, and rs3732360) reported only in a single original study were all from Chinese patients, 20,[22][23][24] and no genotypes were found to be significantly related to ATDH, except one SNP, rs2276707, under the recessive model (OR = 0.600, 95% CI: 0.364-0.988, P = .045). 24 Additionally, there was no evidence for a significant association between six SNPs (ie, rs3814055, rs7643645, rs13059232, rs2461823, rs3814057, and rs6785049) and the risk of ATDH in the allele comparison model (Table 3).…”
Section: Quantitative Analysismentioning
confidence: 98%
See 3 more Smart Citations